Success Rate of Frozen Embryo Transfer through Assisted Hatching Laser Method and Tyrode Acid Chemical Method in Day 3 and 5 Embryos - Hartini, Prastuti Dwi; Lisa, Lucy; Nurcahya, Harini; Irmansyah, Frizar; Gunarwati, Deka Putri (Journal La Lifesci, 2024)
Repeated implantation failures in IVF, aging in women and vitrification at low temperatures cause the embryonic zona pellucida to harden.Technique assisted hatching (AH) laser and chemical methods of tyrode acid can help the process hatching in embryos in improving implantation. The purpose of this study is to determine the relationship between pregnancy success through AH laser method and chemical method of tyrode acid at the embryonic stage day to-3 (D3) and day to-5 (D5) on Frozen Embryo Transfer (FET). The study used a retrospective cohort with a population of 95 patients using AH laser method and 36 patients with tyrode acid chemistry. The results showed the incidence of pregnancy in laser treatment in 27 patients (28.4%) and 14 patients (38.9%) in chemical treatment. Data analyzed by statistical tests Chi-square with a 95% confidence degree and a p< value of 0.05. Exist The relationship between the incidence of pregnancy FET D3 and FET D5 laser treatment, but in chemical treatment no significant difference was found. Logistic regression modeling tests show the chemical method FET D5 has a greater chance of pregnancy of 0.277 than FET D3, will but insignificant with a p-value of >0.05, while the FET D5 laser stage method has a chance of 0.143 significantly higher than FET D3 with a p-value of <0.05.